Parametric Study on a Performance of a Small Counter-Rotating Wind Turbine - Michał Pacholczyk; Dariusz Karkosiński (Energies, 2020)
A small Counter-Rotating Wind Turbine (CRWT) has been proposed and its performance has been investigated numerically. Results of a parametric study have been presented in this paper. As parameters, the axial distance between rotors and a tip speed ratio of each rotor have been selected. Performance parameters have been compared with reference to a Single Rotor Wind Turbine (SRWT). Simulations were carried out with Computational Fluids Dynamics (CFD) solver and a Large Eddy Scale approach to model turbulences. An Actuator Line Model has been chosen to represent rotors in the computational domain. Summing up the results of simulation tests, it can be stated that when constructing a CRWT turbine, rotors should be placed at a distance of at least 0.5 D (where D is rotor outer diameter) or more. One can then expect a noticeable power increase compared to a single rotor turbine. Placing the second rotor closer than 0.5 D guarantees a significant increase in power, but in such configurations, dynamic interactions between the rotors are visible, resulting in fluctuations in torque and power. Dynamic interactions between rotor blades above 0.5 D are invisible.